(untitled) (ENTHYMEMA, 2015)
The article explains the goals of the work on a new historical-philological resource – Index «Fic- tion». It combined all references of the literary texts in the «Chronicle of Current Events», the samizdat newsletter which was published by Moscow intellectuals in 1968-1983.